Effect of Dilute Magnetism in a Topological Insulator - Kabir, Firoza; Hosen, M. Mofazzel; Ding, Xiaxin; Lane, Christopher; Dhakal, Gyanendra; Liu, Yangyang; Dimitri, Klauss; Sims, Christopher; Regmi, Sabin; Sakhya, Anup Pradhan; Persaud, Luis; Beetar, John E.; et al. (Frontiers in Materials, 2021)
Three-dimensional topological insulator (TI) has emerged as a unique state of quantum matter and generated enormous interests in condensed matter physics. The surfaces of a three dimensional (3D) TI consists of a massless Dirac cone, which is characterized by the Z2 topological invariant. The introduction of magnetism on the surface of a TI is essential to realize the quantum anomalous Hall effect and other novel magneto-electric phenomena. Here, by using a combination of first-principles calculations, magneto-transport, and angle-resolved photoemission spectroscopy (ARPES) we study the electronic properties of gadolinium (Gd)-doped Sb2Te3. Our study shows that Gd doped Sb2Te3 is a spin-orbit-induced bulk band-gap material, whose surface is characterized by a single topological surface state. Our results provide a new platform to investigate the interactions between dilute magnetism and topology in magnetic doped topological materials.